Interplay between circadian rhythm, ageing and neurodegenerative disorder - Aarti Nagayach; Rakesh Bhaskar; Shampa Ghosh; Dhivyadharshni M; Mosleh Mohammad Abomughaid; Sung Soo Han; Krishna Kumar Singh; Abdulmajeed G. Almutary; Kamlesh Chaudhary; Shikha Atteri; Ashish Singh Chauhan; Niraj Kumar Jha; et al. (Open Biology)
Circadian rhythm, as a homeostatic tool of biological life, plays a vital role in regulating human physiology, metabolism, endocrinology, and emotional and cognitive behaviour. A disrupted circadian rhythm, marked by age-related alterations such as decreased variation in sleep–wake patterns and instability in the timing of these patterns, can worsen age-related problems such as increased oxidative stress and inflammation. Advancing age is associated with anomalies in the redox balance, gradual alterations in physiological functions and deregulation of various metabolic pathways. The mutual interaction between circadian rhythm and ageing may potentially contribute to the development of neurodegenerative disorders. Consistent alterations in circadian rhythms could lead to various degenerative disorders and aggravate age-related ailments. Therefore, understanding and unravelling the intricate interplay between circadian rhythm and ageing holds immense potential for developing therapeutic interventions and promoting healthy ageing strategies. In this review article, we discuss the role of circadian rhythms in physiology and their age-related changes that impact health. We focus on how disruptions in circadian rhythms, common with ageing, may increase risks for neurodegenerative disorders. Understanding this interaction holds promise for developing therapeutic approaches to support healthy ageing.